PEMISAHAN SITRONELAL DARI MINYAK SEREH WANGI MENGGUNAKAN UNIT FRAKSIONASI SKALA BENCH - Egi Agustian, Anny Sulaswatty, Tasrif, Joddy Arya Laksmono dan Indri Badria Adilina (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTIsolation of citronellal from citronella oil has been studied by using bench scale (2-6 L) fractionation unit. The column used has packed with 120 stages and equipped with a reflux unit. The separation processes were based on temperature, the variation of vacuum pressure 40, 60, 80 mmHg and reflux ratio 10:10, 20:10, 30:10. The optimum condition was obtained at reflux ratio 20:10 and vacuum pressure 60 mmHg with yield of 41.33%. Chromatography analysis showed that isolate has citronellal content about 96.103%.  Keyword: citronella oil, citronellal, fractionation